Comparative analysis of the methods used for finding surface energy to investigate protein interaction behavior on chromatographic supports. (6th May 2019) - Aasim, Muhammad; Khan, Muhammad H.; Rahman, Inam U.; Bibi, Noor Shad; Ali, Waqar; Khan, Nadir Z.; Khan, Abid A.
Abstract: Hydrophobic interaction chromatography, an important and effective purification strategy, is generally used for the purification of variety of biomolecules. A basic understanding of the protein interaction behavior is required to effectively separate these biomolecules. A colloidal type extended Derjaguin, Landau, Verwey, and Overbeek calculations were utilized to study the interactions behavior of model proteins to commercially available hydrophobic chromatographic materials that is, Toyopearl Phenyl 650C and Toyopearl Butyl 650C. Physicochemical properties of selected model proteins were achieved by contact angle and zeta potential measurements. The contact angle of chromatographic materials used was achieved through sessile drop method on disrupted beads and capillary penetration method (CPM) on intact beads. The surface properties were further used to calculate the interactions of the proteins to chromatographic supports. The calculated secondary energy minimum of the proteins with the chromatographic materials (from the contact angle values determined through both methods can be correlated with the retention volumes from the real chromatography. The secondary energy minimum values are higher for each protein to the chromatographic materials calculated from the inputs derived through sessile drop method compared to CPM. For instance, immunoglobulin G has secondary energy minimum value of 0.17 kT compared to 0.11 kT, obtained through sessile drop method and CPM, respectively. Average relative values of the energy minimum calculated for all proteins are as 1.51 kT and 1.29 kT for Toyopearl Butyl 650C and Toyopearl Phenyl 650C, respectively, as a conversion factor for estimation of secondary energy minimum for both methods.